2018
DOI: 10.1021/jacs.8b02948
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasmooth Quantum Dot Micropatterns by a Facile Controllable Liquid-Transfer Approach: Low-Cost Fabrication of High-Performance QLED

Abstract: Fabrication of a high quality quantum dot (QD) film is essentially important for a high-performance QD light emitting diode display (QLED) device. It is normally a high-cost and multiple-step solution-transfer process where large amounts of QDs were needed but with only limited usefulness. Thus, developing a simple, efficient, and low-cost approach to fabricate high-quality micropatterned QD film is urgently needed. Here, we proposed that the Chinese brush enables the controllable transfer of a QD solution dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
86
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 56 publications
0
86
0
Order By: Relevance
“…Electroluminescent (EL) devices have been the research hotspots for decades because of their enormous market value in lighting sources and displays . In particular, tremendous efforts have been put into developing the cost‐effective fabrication approaches for eco‐friendly illumination units, such as organic light‐emitting diodes (OLEDs) and quantum dots based light‐emitting diodes (QLEDs) .…”
Section: Introductionmentioning
confidence: 99%
“…Electroluminescent (EL) devices have been the research hotspots for decades because of their enormous market value in lighting sources and displays . In particular, tremendous efforts have been put into developing the cost‐effective fabrication approaches for eco‐friendly illumination units, such as organic light‐emitting diodes (OLEDs) and quantum dots based light‐emitting diodes (QLEDs) .…”
Section: Introductionmentioning
confidence: 99%
“…Then, the H 3 PO 4 –PVA electrolyte was applied one more time to ensure that the two electrodes are electrically connected. On the twisted structure fiber supercapacitor, triboelectric polymer poly(vinylidenefluoride‐trifluoroethylene‐chlorotrifluoroethylene) (P(VDF‐TrFE‐CTFE)) solution at a concentration of 10 wt.% was coated using the brush printing method, which resulted in a coaxial structure fiber device, namely, a spontaneous self‐charging hybrid smart fiber . It is found that the brush printing method demonstrated excellent feasibility of replacing the conventional spin‐coating method.…”
Section: Resultsmentioning
confidence: 99%
“…First, carbon fibers with the diameter of ≈7 µm were well aligned in the vertical direction and then a bundle of carbon fibers was polished using deionized water in order to make a carbon fiber electrode with the thickness of 500 µm. On the carbon fibers, a phosphoric acid (H 3 PO 4 ) electrolyte mixed with polyvinyl alcohol (PVA) was applied using a brush printing method . After 2 h of a drying process in ambient air at room temperature, two carbon electrodes with the H 3 PO 4 –PVA electrolyte were twisted together with a period of 5 turns per inch.…”
Section: Resultsmentioning
confidence: 99%
“…To date, solution processes have been widely used for fabricating QD films because they involve mild conditions and easy operation, such as contact printing, spin coating, screen printing, roll‐to‐roll coating, blade coating, inkjet printing, and others . However, these approaches normally suffer from the limitations of either high‐cost or low film quality.…”
Section: Summary Of the Performance Of The As‐prepared Qled Devices (mentioning
confidence: 99%